Differences in food intake of tumour‐bearing cachectic mice are associated with hypothalamic serotonin signalling. Issue 1 (31st March 2015) - Dwarkasing, Jvalini T.; Boekschoten, Mark V.; Argilès, Joseph M.; van Dijk, Miriam; Busquets, Silvia; Penna, Fabio; Toledo, Miriam; Laviano, Alessandro; Witkamp, R. F.; van Norren, Klaske
Abstract: Background: Anorexia is a common symptom among cancer patients and contributes to malnutrition and strongly impinges on quality of life. Cancer‐induced anorexia is thought to be caused by an inability of food intake‐regulating systems in the hypothalamus to respond adequately to negative energy balance during tumour growth. Here, we show that this impaired response of food‐intake control is likely to be mediated by altered serotonin signalling and by failure in post‐transcriptional neuropeptide Y (NPY) regulation. Methods: Two tumour cachectic mouse models with different food intake behaviours were used: a C26‐colon adenocarcinoma model with increased food intake and a Lewis lung carcinoma model with decreased food intake. This contrast in food intake behaviour between tumour‐bearing (TB) mice in response to growth of the two different tumours was used to distinguish between processes involved in cachexia and mechanisms that might be important in food intake regulation. The hypothalamus was used for transcriptomics (affymetrix chips). Results: In both models, hypothalamic expression of orexigenic NPY was significantly higher compared with controls, suggesting that this change does not directly reflect food intake status but might be linked to negative energy balance in cachexia. Expression of genes involved in serotonin signalling showed to be different between C26‐TB mice and Lewis lung carcinoma‐TB mice and was inversely associated with food intake. In vitro, using hypothalamic cell lines, serotonin repressed neuronal hypothalamic NPY secretion while not affecting messenger NPY expression, suggesting that serotonin signalling can interfere with NPY synthesis, transport, or secretion. Conclusions: Altered serotonin signalling is associated with changes in food intake behaviour in cachectic TB mice. Serotonins' inhibitory effect on food intake under cancer cachectic conditions is probably via affecting the NPY system. Therefore, serotonin regulation might be a therapeutic target to prevent the development of cancer‐induced eating disorders.